LECTURER SOCIALIZATION MODEL IN TRANSFERRING CHARACTER BUILDING MESSAGES AT ISLAMIC HIGH SCHOOL IN ACEH TAMIANG - Dinda Rizky Amalia (Media Inovasi Pendidikan dan Publikasi, 2023)
This study aims to describe the socialization of lecturers in transferring messages of character building to the Aceh Tamiang Islamic high school. The purpose of this research is as a form of education and information to readers that Islamic tertiary institutions have the task of forming the moral, mental and spiritual character of students based on Islamic religious guidance. The type of writing for this article is qualitative research that seeks to describe and describe what is happening as it is and then describe it in a structured and systematic manner by following the applicable rules of writing scientific papers. From the results of research that has been done, it was found that. First, the Aceh Tamiang Islamic high school plays an important role by optimizing the campus as the epicenter of character building. Second, the Aceh Tamiang Islamic high school as a center for the establishment of religious moderation in the midst of societal pluralism. Third, the Aceh Tamiang Islamic High School makes lecturers not only as educators for students to improve intellectually but also as agents for forming students' moral and spiritual character. Fourth. Lecturer at the Aceh Tamiang Islamic High School is committed to being the front guard in protecting the nation's religion and morals.